2019
DOI: 10.2106/jbjs.19.00889
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Association of Gabapentinoids with Pulmonary Complications After Total Hip and Knee Arthroplasties

Abstract: Background: Gabapentinoids are commonly prescribed in perioperative multimodal analgesia protocols. Despite widespread use, the optimal dose to reduce opioid consumption while minimizing risks is unknown. We assessed dose-dependent effects of gabapentinoids on opioid consumption and postoperative pulmonary complications following total hip or knee arthroplasty (THA or TKA). We hypothesized that use of a gabapentinoid on the day of THA or TKA is associated with an increased risk of postoperative pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…A third retrospective analysis found preoperative gabapentin exposure was associated with a 47% increase in odds of experiencing a postoperative respiratory event, though the vast majority of the studied population were administered doses exceeding 300 mg [190,191]. Gabapentinoids exhibit dose-dependent propensity to increase postoperative pulmonary complications, though combination with other multimodal agents may negate this risk, and the absolute risk of adverse events with perioperative gabapentinoids appears low [177,192,193]. Hence, adverse event risks of gabapentinoids can be substantially mitigated by using conservative doses (i.e., 300 mg gabapentin preoperatively), avoiding postoperative use in patients experiencing or at risk for sedation or dizziness, and/or avoiding entirely in high-risk patients.…”
Section: Preoperative Phasementioning
confidence: 99%
“…A third retrospective analysis found preoperative gabapentin exposure was associated with a 47% increase in odds of experiencing a postoperative respiratory event, though the vast majority of the studied population were administered doses exceeding 300 mg [190,191]. Gabapentinoids exhibit dose-dependent propensity to increase postoperative pulmonary complications, though combination with other multimodal agents may negate this risk, and the absolute risk of adverse events with perioperative gabapentinoids appears low [177,192,193]. Hence, adverse event risks of gabapentinoids can be substantially mitigated by using conservative doses (i.e., 300 mg gabapentin preoperatively), avoiding postoperative use in patients experiencing or at risk for sedation or dizziness, and/or avoiding entirely in high-risk patients.…”
Section: Preoperative Phasementioning
confidence: 99%
“…4,5,24 It also highlights the importance of the overall benefit-risk assessment when considering adjuvant use of gabapentinoids, which have been shown to be associated with a decrease in postoperative pain and opioid consumption, although not consistently. 2,4,25 A 2020 observational study 21 found no association between gabapentinoids and reduced opioid consumption either on the day of or the day after total knee or hip arthroplasty. A randomized clinical trial that observed patients after discharge 25 found that perioperative gabapentin had no effect on postoperative pain resolution, although it had some effect on promoting opioid cessation after surgery.…”
Section: Jama Network Open | Surgerymentioning
confidence: 99%
“…Using this protocol, the authors found a significant decrease in postoperative pain coupled with lower oral opioid consumption when compared with a historical opioidbased regimen. There are new concerns regarding potential adverse perioperative effects with gabapentinoids including pulmonary complications (30,31). At our institution, colleagues in anesthesia have expressed similar concerns.…”
Section: Discussionmentioning
confidence: 82%